2005
DOI: 10.2165/00007256-200535120-00004
|View full text |Cite
|
Sign up to set email alerts
|

Exercise-Induced Oxidative Stress

Abstract: Although assays for the most popular markers of exercise-induced oxidative stress may experience methodological flaws, there is sufficient credible evidence to suggest that exercise is accompanied by an increased generation of free radicals, resulting in a measurable degree of oxidative modifications to various molecules. However, the mechanisms responsible are unclear. A common assumption that increased mitochondrial oxygen consumption leads per se to increased reactive oxygen species (ROS) production is not … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

4
92
1
2

Year Published

2007
2007
2024
2024

Publication Types

Select...
8
2

Relationship

0
10

Authors

Journals

citations
Cited by 261 publications
(99 citation statements)
references
References 176 publications
4
92
1
2
Order By: Relevance
“…Excessive levels of ROS may alter the muscle, mainly through inflammatory processes (28). Levels of DCF-RS were increased in the SEP group; however, the SEP+CWI group did not present an increment, which demonstrated that CWI may prevent the DCF-RS increase caused in our protocol of exercise-induced exhaustion.…”
Section: Discussionmentioning
confidence: 99%
“…Excessive levels of ROS may alter the muscle, mainly through inflammatory processes (28). Levels of DCF-RS were increased in the SEP group; however, the SEP+CWI group did not present an increment, which demonstrated that CWI may prevent the DCF-RS increase caused in our protocol of exercise-induced exhaustion.…”
Section: Discussionmentioning
confidence: 99%
“…Furthermore the current study employed eccentric exercise and may highlight a differential oxidative response to fish oils with varying modes of exercise. Indeed it is likely that the mechanisms through which reactive oxygen species are generated will depend upon the mode of exercise employed (Vollaard et al, 2005) and so any modulation of these mechanisms (e.g., via fish oil-derived n-3 PUFAs) will be dependent upon the exercise mode employed. However, as the precise mechanisms responsible for exercise-induced free radical production, under these various exercise modes, remains to be elucidated, uncovering the mechanisms underlying the findings of the current studies are problematic.…”
Section: Discussionmentioning
confidence: 99%
“…Qualitative muscle changes might relate to the observed difference in muscle performance. Muscle contraction is influenced by a variety of factors, including muscle fiber type, pH, sarcoplasmic reticulum function, and energy supply, and the functions of proteins involved in these processes is affected by oxidative stress (Smith and Reid 2006;Vollaard et al 2005). The higher oxidative stress observed in SAMP1 controls is considered to be a cause of their accelerated senescence and aging-related alterations in cell function (Hosokawa 2002).…”
Section: Discussionmentioning
confidence: 99%